Manpower problems and economic development in Nigeria: report - Yesufu, T. M. (Ibadan: Published for the Nigerian Institute of Social and Economic Research [by] Oxford University Press, 1969)
This book is the outcome of the deliberations of an international seminar which met in Lagos in march 1964 to consider the nature of Nigeria's manpower problems with special reference to the needs of economic development.
Selected papers from the seminar.
Includes bibliographical references.
oo 09/08/2018
Loans
Keywords: Manpower policy; Labor supply